2018
DOI: 10.31272/jeasd.2018.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Thin RPC Wall Panels With Varying Steel Reinforcement and Aspect Ratio Subjected to Axial Eccentric Uniformly Distributed Loading

Abstract: This paper presents experimental study of structural behavior of thin Reactive Powder Concrete (RPC) wall panels subjected to axial eccentric uniformly distributed loading with varying steel reinforcement ratio (ρ) and aspect ratio (AR= H/L). The experimental program included testing of six two-way thin RPC wall panels, fixed at all sides and applying the load axially with eccentricity equal to (t/6). The results indicates that the ultimate strength of the RPC wall panel decreases with increase in AR from (1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The maximum lateral loads ranged from 17.81 kN to 20.25 kN and 124.06 kN to 152.33 kN for framed and ICF wall panels, respectively. These experiments showed that ICF wall panels could resist higher lateral loads than the various framed wall panels that were tested [13,14]. Reinforced concrete openings in wall panels with slenderness ratios of 30, 35, and 40 were tested under uniformly distributed axial loads in one-way and two-way directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum lateral loads ranged from 17.81 kN to 20.25 kN and 124.06 kN to 152.33 kN for framed and ICF wall panels, respectively. These experiments showed that ICF wall panels could resist higher lateral loads than the various framed wall panels that were tested [13,14]. Reinforced concrete openings in wall panels with slenderness ratios of 30, 35, and 40 were tested under uniformly distributed axial loads in one-way and two-way directions.…”
Section: Introductionmentioning
confidence: 99%
“…The loads increased in the higher range of normal concrete strength, while the opposite effect occurred in the RPC wall panels. The deflections increased in the higher aspect ratios of the normal concrete wall panels, while the opposite effect occurred in the RPC wall panels [14]. Previous studies have used various dimensions of wall panels; these include concrete wall panels with lengths and heights of 1200 mm, 1400 mm, and 1600 mm and all having the same 40 mm thickness.…”
Section: Introductionmentioning
confidence: 99%